Felícitas López Portillo T., Salvador Méndez Reyes y Laura Muñoz Mata, Bajo el manto del libertador. Relaciones de México con Colombia, Panamá y Venezuela 1821-2000, Felícitas López Portillo T. [coord.], México, SRE, 2004, 277 pp. - Rodríguez Díaz, María del Rosario (Latinoamérica. Revista de Estudios Latinoamericanos, 2020)
Reseña del libro: Felícitas López Portillo T., Salvador Méndez Reyes y Laura Muñoz Mata, Bajo el manto del libertador. Relaciones de México con Colombia, Panamá y Venezuela 1821-2000, Felícitas López Portillo T. [coord.], México, SRE, 2004, 277 pp.